2018
DOI: 10.1186/s13104-018-3683-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with latrine utilization among model and non-model families in Laelai Maichew Woreda, Aksum, Tigray, Ethiopia: comparative community based study

Abstract: ObjectiveThe study was conducted on 313 model and 313 non model households to assess latrine utilization and factors affecting among model and non-model families.ResultAbout 225 (71.9%) model and 144 (46%) non-model participants declared that they utilize their latrine which gave the overall utilization rate of 369 (58.9%). Households with primary and above education were two times (AOR = 2.03, 95% CI 1.427, 4.638) more likely to utilize latrine as compared with illiterate households. Cleanness of the latrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
23
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 29 publications
17
23
3
Order By: Relevance
“…Our study indicated that a household family size of one to three persons was one of the determinant factor for latrine utilization, a finding consistent with similar studies in other areas of Ethiopia such as in Southeast Zone of Tigray [30] and in Hawassa [31]. Sharing one…”
Section: Discussionsupporting
confidence: 90%
“…Our study indicated that a household family size of one to three persons was one of the determinant factor for latrine utilization, a finding consistent with similar studies in other areas of Ethiopia such as in Southeast Zone of Tigray [30] and in Hawassa [31]. Sharing one…”
Section: Discussionsupporting
confidence: 90%
“…Regarding latrine utilization, it was higher than evidence from systematic reviews at the national level (37.7%), Central zone of Tigray, Northern Ethiopia (58.9%), Awabel district of Amhara region (52%), and Gulomekeda of Tigray region (57.3%) [8,9,19,28]. Latrine location inside the house compound was four times more likely utilized by household members (AOR � 4.463, 95% CI: 1.021-19.516).…”
Section: Discussionmentioning
confidence: 73%
“…However, the reported findings were with highly varying figures. Regarding latrine utilization, more than half (59.8%) was reported from the La'ilay Maichew district of central Tigray and Enderta district of Mekelle Zone (68.4%) that showed a significant variability [9,10]. Meanwhile, latrine prevalence was only reported from South Eastern part of Tigray (53%) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in Public Hospitals of Central, North West and Western zone of Tigray. Tigray is one region of Ethiopia which covers an area of 109 km 2 and its elevation is 2084 M above sea level [ 15 25 ]. Institutional based cross-sectional study was conducted to assess the knowledge, attitude, and practice towards blood donation and its associated factors among health professionals in Public Hospitals of Central, North West and Western zone of Tigray from August to September 2016.…”
Section: Main Textmentioning
confidence: 99%